Long-term adaptation mitigates the promotion effect of air pollution on short-term population movements - Luo, Chongjia; Yan, Xiaotong; Wang, Bowen; Ali, Abdelrahman (Frontiers in Environmental Science, 2025)
IntroductionWhile permanent migration has been extensively studied as a health-protective strategy for residents to avoid air pollution, national-level evidence regarding the short-term movement as a potentially more cost-effective measure remains limited.MethodsThis study used the instrumental variable approach to empirically examine the effect and mechanism of air pollution on short-term population movements in China by using a cross-city daily panel dataset.ResultsOur results showed that air pollution significantly promotes short-term population movements. A 100-unit increase in the air quality index at the origin city relative to the destination city led to an 8% rise in short-term movements. Residents tended to relocate only after pollution events occurred. The willingness to temporarily escape from air pollution was stronger under lower economic constraints, with more recreational opportunities and more available time. Moreover, long-term adaptation to historical air pollution weakened residents’ willingness to leave in response to local pollution events, reducing the potential health benefits of short-term movements by 44.49%.DiscussionThis study provides valuable insights into the motivations and mechanisms of residents’ decisions to temporarily relocate to feasibly and flexibly reduce pollution exposure and related health risks.